1984
DOI: 10.1002/star.19840360602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Temperature During Development of Rice Plants on Some Properties of Endosperm Starch

Abstract: Starch granules were isolated from polished grains of rice plants (Oriza sativa L.) grown under controlled temperature conditions. Distribution of isoamylase‐debranched starch materials and unit chain‐length of amylopectin were examined by gel‐filtration on columns. Higher environment temperature decreases amylose concentration in endosperm starches of Japanese rice cultivars. The amylose concentration in the endosperm starch is determined by the environment temperature 5 – 15 days after heading. Interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
82
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(96 citation statements)
references
References 11 publications
13
82
1
Order By: Relevance
“…These results suggest that the ambient temperature likely affects the varietal characteristics of the starch properties associated with the gelatinization temperature during the maturation period. A similar relationship between the ambient temperature during the maturation period and the gelatinization temperature was also reported in rice starch (Asaoka et al, 1984;Okuda et al, 2009) and amylose content in rice grains (Resurreccion et al, 1977;Sano et al, 1985;Yamakawa et al, 2007). It was reported that the fine structure of amylopectin changed with ambient temperature during the maturation period together with gene expression patterns and enzyme activity levels associated with starch synthesis (Inouchi et al, 2000;Jiang et al, 2003;Umemoto et al, 1999;Yamakawa et al, 2007).…”
Section: Variability In Starch Properties Under Different Ambient Temsupporting
confidence: 71%
“…These results suggest that the ambient temperature likely affects the varietal characteristics of the starch properties associated with the gelatinization temperature during the maturation period. A similar relationship between the ambient temperature during the maturation period and the gelatinization temperature was also reported in rice starch (Asaoka et al, 1984;Okuda et al, 2009) and amylose content in rice grains (Resurreccion et al, 1977;Sano et al, 1985;Yamakawa et al, 2007). It was reported that the fine structure of amylopectin changed with ambient temperature during the maturation period together with gene expression patterns and enzyme activity levels associated with starch synthesis (Inouchi et al, 2000;Jiang et al, 2003;Umemoto et al, 1999;Yamakawa et al, 2007).…”
Section: Variability In Starch Properties Under Different Ambient Temsupporting
confidence: 71%
“…The heading date of NIL(Wx a ) was 6 days later and the temperature during grain filling was 1.2ºC lower than those of Nipponbare. The temperature during grain fi lling clearly affects amylose content of rice with the Wx b allele, but not that of rice with the Wx a allele (Asaoka et al, 1984;Hirano and Sano, 1998;Umemoto and Terashima, 2002). Rice grains that mature at a lower temperature have amylopectin rich in short chains (Umemoto et al, 1999;Inouchi et al, 2000), presumably through changes in branching enzyme activities (Jiang et al, 2003).…”
Section: Characterization Of Nils In Relation To Starchmentioning
confidence: 99%
“…In rice grains ripened at a low temperature, amylose content was higher (Inatsu, 1979;Asaoka et al, 1985;Tamaki et al, 1989;Koseki et al, 2004), and the gelatinization onset, peak and concluding temperatures and enthalpy measured with DSC were lower than those in the grains ripened at a high temperature (Asaoka et al, 1984(Asaoka et al, , 1985. Although the difference in heading and maturity date among Hattan-type varieties were observed (Table 3), no signifi cant varietal difference was observed in either amylose content or the gelatinization properties measured with DSC ( Fig.…”
Section: Resultsmentioning
confidence: 85%